Multi-switching combination synchronization of different fractional-order non-linear dynamical systems. (2nd October 2018) - Bhat, Muzaffar Ahmad; Khan, Ayub
Abstract: In this paper, multi-switching combination synchronization (MSCS) scheme has been investigated between a class of three non-identical fractional-order chaotic systems. The fractional-order Lorenz and Chen System are taken as drive systems. The combination of multi drive systems is then synchronized with the fractional-order Rössler chaotic system. In MSCS, the state variables of two drive systems synchronize with different state variables of response system, simultaneously. Based on the stability of fractional-order chaotic systems, the multi-switching combination synchronization of three fractional-order non-identical systems has been investigated. For the synchronization of three non-identical fractional-order chaotic systems suitable controllers have been designed. Theoretical analysis and numerical results are presented to demonstrate the validity and feasibility of the applied method.